2018
DOI: 10.1371/journal.pone.0193215
|View full text |Cite
|
Sign up to set email alerts
|

Practice makes the deficiency of global motion detection in people with pattern-related visual stress more apparent

Abstract: AimsPattern-related visual stress (PRVS) refers to the perceptual difficulties experienced by some individuals when exposed to high contrast striped patterns. People with PRVS were reported to have reduced sensitivity to global motion at baseline testing and the difference disappears at a second estimate. The present study was to investigate the effect of practice on global motion threshold in adults with and without PRVS.MethodsA total of 101 subjects were recruited and the Wilkins & Evans Pattern Glare Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The result of increased excitability in the visual cortex of MDD patients is consistent with the findings of recent psychophysical research, in which heightened levels of pattern glare were observed in MDD, reflecting an increase in cortical excitability (20). The neurological mechanism driving pattern glare is usually assumed to be of cortical origin, i.e., cortical hyper-excitability or inadequate cortical inhibition caused by a lack of inhibitory systems unable to restrain overexcited situations (32)(33)(34). Previous research on cortical excitability in MDD has relied mostly on TMS, which is commonly utilized to evaluate motor cortical excitability, and found an interhemispheric imbalance between the prefrontal and motor cortex, which manifested as decreased excitability in the left hemisphere and increased excitability in the right (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 85%
“…The result of increased excitability in the visual cortex of MDD patients is consistent with the findings of recent psychophysical research, in which heightened levels of pattern glare were observed in MDD, reflecting an increase in cortical excitability (20). The neurological mechanism driving pattern glare is usually assumed to be of cortical origin, i.e., cortical hyper-excitability or inadequate cortical inhibition caused by a lack of inhibitory systems unable to restrain overexcited situations (32)(33)(34). Previous research on cortical excitability in MDD has relied mostly on TMS, which is commonly utilized to evaluate motor cortical excitability, and found an interhemispheric imbalance between the prefrontal and motor cortex, which manifested as decreased excitability in the left hemisphere and increased excitability in the right (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 85%
“…The number of these perceived experiences reported was summed to provide a pattern glare score of each pattern [ 37 ]. The mid-high SF difference variable was obtained by subtracting the mid-SF score from the high-SF score and was also included in the analysis [ 38 ]. Participants with higher pattern glare scores were supposed to have more severe pattern glare [ 13 ].…”
Section: Methodsmentioning
confidence: 99%